THE SYMBOLIC MEANING OF SONGKET WEAVING CULTURAL HISTORY IN GROWING AWARENESS OF HISTORY IN METHODIST 04 BANYUASIN III HIGH SCHOOL STUDENTS - Samosir, Sarah Pratiwi; Nindiati, Dina Sri; Zamhari, Ahmad; Suriadi, Aan (International Conference On Social Science Education, 2023)
Symbolic meaning is a whole series of things related to meaning and the study of signs that have their own meaning. Songket woven fabric is a craft created by the creation of cultural arts that must be maintained and preserved. Songket cloth has different symbolic meanings. Problem Formulation How the Symbolic Meanings of Songket Weaving Cultural History Can Grow Students' Historical Awareness at Methodist 04 Banyuasin High School III. From the problem the researcher has the aim of this study to find out the symbolic meaning of the cultural history of Songket Weaving, to find out the historical awareness of Methodist 04 Banyuasin III high school students. The research method used in this study is a qualitative descriptive method and data collection techniques using observation, interviews, documentation questionnaires and literature study. The results of the study are to get students' understanding of the value of historical awareness, that students do not understand about songket cloth so researchers must introduce songket cloth so as to foster awareness of the history of songket cloth.